Thermal tourism: study of the profile and motivations of the practitioner in portugal - Loureiro, Isabel Sofia (2020)
Health and wellness tourism had a growing interest in the Portuguese population until 2019. However, with the ap-pearance of Covid-19, several establishments had to close over these two years, this segment being one of the most affected areas. Many water users looked forward to the opening of the spa resorts to continue their treatments. Giv- en the importance of this theme, this work has as its main goal the definition of a consumer profile and to identify the determinants of satisfaction of the thermal tourists, as well as to gauge the degree of knowledge of thermal tourism and specifically of spas in the Portuguese context. In methodological terms, a questionnaire survey was conducted among the tourists to achieve the research objectives. The results show a younger, healthier and diversified thermal tourism practitioner. It also reveals similarities with other profile and motivations studies. However, it is possible to notice a few differences. Practitioners are seeking a combination of a leisure and health dimension and valorise fac- tors such as location and access of the establishments, quality of the services provided and rest and tranquillity. An issue regarding their length of stay has been identified. As they are locals and live in the same country as the thermal spa, most respondents do not stay overnight at the destination. In the future, it would be interesting to research product development and market strategies for diversified thermal practitioners.